1995
DOI: 10.2535/ofaj1936.72.5_259
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analyses and Aging Process of Nerve Fibers in the Human Spinal Posterior Funiculus

Abstract: Summary:The Changes in the nervous system associated with age are receiving increasing attention in all research fields of medical science. However, there are few references on the correlation between age and morphometric analysis of the spinal cord. The age-related findings in humans so far have been: the length and caudal level of termination (Hara, 1987), the crosssectional area and diameter (Bailey, 1953;Tanaka, 1984;Sasaki et al. , 1994), and the number of motor neurons of the spinal cord (Tomlinson and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Zhang et at 14) found that an atrophy and a decrease in number of myelinated axons were the main changes connected with ageing occurring in the human spinal cord. However, the clinical appearance of the small splanchnic nerve in relation to the ageing process still remains unknown and should be elucidated in future.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et at 14) found that an atrophy and a decrease in number of myelinated axons were the main changes connected with ageing occurring in the human spinal cord. However, the clinical appearance of the small splanchnic nerve in relation to the ageing process still remains unknown and should be elucidated in future.…”
Section: Discussionmentioning
confidence: 99%
“…However, no evaluation of nerve fibers in the LCST is included in the literature regarding the cervical levels, apart from decrease with age of the number of axons in the posterior funiculus at the C6 level 7) . At the C5 level, we found similar results in the LCST, which contains axons innervating the anterior horn cells supplying the upper and lower extremities, compared to the data concerning the L1 level 1,2) .…”
Section: Discussionmentioning
confidence: 99%
“…A morphometric analysis was conducted to detect the aging of nerve fibers in the human spinal posterior funiculus 37 . Thirty‐eight spinal cords were taken from cadaver specimens (25 males and 13 females) aged from 41 to 97 years.…”
Section: Aging Processmentioning
confidence: 99%